Genetic diversity of Iranian honey bee (Apis mellifera meda Skorikow, 1829) populations based on ISSR markers - Rahimi, A; Mirmoayedi, A; Kahrizi, D; Zarei, L; Jamali, S (Cellular and Molecular Biology, 2016)
Honey bee is one of the most important insects considering its role in agriculture,ecology and economy as a whole. In this study, the genetic diversity of different Iranian honey bee populations was evaluated using inter simple sequence repeat (ISSR) markers. During May to September 2014, 108 young worker honey bees were collected from six different populations in 30 different geoclimatic locations from Golestan, Mazendaran, Guilan, West Azerbaijan, East Azerbaijan, Ardebil provinces of Iran. DNA was extracted from the worker honey bees. The quality and quantity of extracted DNA were measured. A set of ten primers were screened with the laboratory populations of honey bees. The number of fragments produced in the different honey bee populations varied from 3 to 10, varying within 150 to 1500 bp. The used ten ISSR primers generated 40 polymorphic fragments, and the average heterozygosity for each primer was 0.266. Maximum numbers of bands were recorded for primer A1. A dendrogram based on the Unweighted Pair Group Method with Arithmetic mean (UPGMA) method generated two sub-clusters. Honey bee populations of Golestan, Mazendaran, Guilan provinces were located in the first group. The second group included honey bee populations of Ardebil, West Azerbaijan, East Azerbaijan provinces, but this group showed a close relationship with other populations. The results showed obviously the ability of the ISSR marker technique to detect the genetic diversity among the honey bee populations.